Queer Theory and Communication : From Disciplining Queers to Queering the Discipline(s). - Yep, Gust A. (Taylor and Francis, 2014)
Get a queer perspective on communication theory! Queer Theory and Communication: From Disciplining Queers to Queering the Discipline(s) is a conversation starter, sparking smart talk about sexuality in the communication discipline and beyond. Edited by members of?The San Francisco Radical Trio,? the book integrates current queer theory, research, and interventions to create a critical lens with which to view the damaging effects of heteronormativity on personal, social, and cultural levels, and to see the possibilities for change through social and cultural transformation. Queer Theo.